Knowledge and Buddhist Integration Tor Taking Care of Terminal Patients - Punyatharo, Phra Bunsong; Peuchthonglang, Prateep (Journal for Developing the Social and Community, 2018)
This research article was aim (1) to study the knowledge about the terminal patients in Buddhism, and (2) to present the Buddhist integration for taking care of the terminal patients. After the researcher had studied data from Tipitaka and commentaries, the researcher analyzed, synthesized, and found that ; The terminal patients are the patients who got the incurable disease, so these patients sometime felt disappointed for their treatment. Moreover, the doctors just tried to treat them with the multiple profession, so they can live in the society. In Buddhism, monks tried to teach patients to have pure, clam and happy minds, so they can leave this world peacefully. However, there are four steps of the Buddhist integration for taking care of the terminal patients as follows (A) to cultivate faith in the Triple Gems for the terminal patients by letting them to perform the Buddhist ceremonies such as offerings and precepts observing etc., (B) to chant the Buddha verse until their minds become tranquil and stable, (C) to chat with the terminal patients for reminding them to be happy with their merit making and to be mindful with their lives, (D) to give a sermon and practice meditation : the terminal patients who interested in Dhamma (sermon), but they cannot talk or respond well, the meditation master only demonstrate the way to practice meditation and letting them to practice meditation easily as they can through the Four Foundations of Mindfulness.